2022
DOI: 10.1001/jamanetworkopen.2022.16910
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Screening Colonoscopy Rates After Positive Noninvasive Testing for Colorectal Cancer in States With and Without Cost-Sharing

Abstract: This cohort study examines the colorectal cancer (CRC) screening rates in 2 US states that have implemented policies to eliminate consumer cost-sharing of CRC screening and compares these rates with those of neighboring states that have not enacted similar policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Policies that eliminate patient cost-sharing for follow-up colonoscopies have been limited to a few states and have been in effect since 2016. The only published real-world study determined colorectal cancer screening rates in Oregon and Kentucky after state-level polices removed cost-sharing for follow-up colonoscopies and then compared the results with neighboring states without similar policies ( 19 ). In Oregon, removing cost-sharing significantly increased the rate undergoing any colorectal cancer screening by 1% and was associated with a significant shift from colonoscopy to a noninvasive screening test for initial screening (e.g., 10% shift from colonoscopy to a noninvasive test).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies that eliminate patient cost-sharing for follow-up colonoscopies have been limited to a few states and have been in effect since 2016. The only published real-world study determined colorectal cancer screening rates in Oregon and Kentucky after state-level polices removed cost-sharing for follow-up colonoscopies and then compared the results with neighboring states without similar policies ( 19 ). In Oregon, removing cost-sharing significantly increased the rate undergoing any colorectal cancer screening by 1% and was associated with a significant shift from colonoscopy to a noninvasive screening test for initial screening (e.g., 10% shift from colonoscopy to a noninvasive test).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Centers for Medicare and Medicaid Services (CMS) finalized their decision to cover follow-up colonoscopy after a positive stool-based colorectal cancer screening test with no cost-sharing for Medicare patients that went into effect on January 2, 2023 ( https://www.cms.gov/newsroom/fact-sheets/calendar-year-cy-2023-medicare-physician-fee-schedule-final-rule ). The clinical and economic impact of this new Medicare Physician Fee Schedule rule is unknown, although a recent study found that a policy that eliminated patient cost-sharing for follow-up colonoscopy after a positive stool-based test in Oregon significantly increased the overall uptake of colorectal cancer screening and shifted screening modalities from colonoscopy to noninvasive methods ( 19 ). The objective of this analysis was to estimate the clinical and economic effects from increased colorectal cancer screening that may stem from the recent CMS policy change eliminating patient cost-sharing for a follow-up colonoscopy after a positive stool test in a cohort of Medicare beneficiaries.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CRC in China is the third most common cancer after lung cancer and stomach cancer [2,3] . The cause of CRC is not known, but the cancer is closely related to family history, dietary habits, heredity, age and disease [4,5] . The clinical presentation of CRC is simple and often appears as symptoms such as changes in the patient's bowel habits, changes in the nature of stools, abdominal pain, abdominal masses and anaemia [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…In the Research Letter titled, “Comparison of Screening Colonoscopy Rates After Positive Noninvasive Testing for Colorectal Cancer in States With and Without Cost-Sharing,” 1 published June 14, 2022, there was an error in the Results and in Table 2. The 95% CI for the odds ratio of patients in Oregon receiving any colorectal cancer screening after policy implementation should have been listed as 1.00 to 1.12.…”
mentioning
confidence: 99%
“…The 95% CI for the odds ratio of patients in Oregon receiving any colorectal cancer screening after policy implementation should have been listed as 1.00 to 1.12. This article has been corrected …”
mentioning
confidence: 99%